Self-Perceived Strengths Among Adolescents With and Without Substance Abuse Problems. (April 2017) - Harris, Nicholas; Brazeau, James N.; Rawana, Edward P.; Brownlee, Keith; Klein, Rupert
The importance of examining positive aspects of youth development has been emphasized across disciplines involved in the care of youth with substance abuse problems. However, little is known about the strengths of adolescents with substance abuse problems, especially youth entering residential treatment. Utilizing the Strengths Assessment Inventory, a measure assessing psychological and social strengths, we examined patterns of strengths across groups of age- and gender-matched youth who reported no substance use, frequent substance use, and those entering treatment for severe substance use. Each group consisted of 43 participants ranging in age from 14 to 18 years. Results indicated that, on average, individuals entering treatment scored lower on personal strengths. However, through the use of more sophisticated statistical approaches, it was found that certain strengths were predictive of individuals belonging to the treatment group. Results are discussed in terms of their relevance to the treatment of adolescent substance abuse problems.